Systemic Lupus Erythematosus (SLE) Complicated by Neuromyelitis Optica (NMO – Devic's Disease): Clinic-Pathological Report and Review of the Literature. Issue 7 (January 2014) - Adawi, Mohammad; Bisharat, Bishara; Bowirrat, Abdalla
Neuromyelitis optica (NMO) is usually a relapsing demyelinating disease of the central nervous system associated with optic neuritis, transverse myelitis involving three or more contiguous spinal cord segments, and seropositivity for NMO-IgG antibody. NMO is often mistaken for multiple sclerosis and there are relatively sporadic publications about NMO and overlapping systemic or organ-specific autoimmune diseases, such as systemic lupus erythematosus (SLE). We described a unique case of a 25-year-old Arab young woman who was diagnosed with SLE, depending on clinical, laboratory investigations and after she had fulfilled the diagnostic criteria for SLE and had presented the following findings: constitutional findings (fatigue, fever, and arthralgia); dermatologic finding (photosensitivity and butterfly rash); chronic renal failure (proteinuria up to 400 mg in 24 hours); hematologic and antinuclear antibodies (positivity for antinuclear factor (ANF), anti-double-stranded DNA antibodies, direct Coombs, ANA and anti-DNA, low C4 and C3, aCL by IgG and IgM). Recently, she presented with several episodes of transverse myelitis and optic neuritis. Clinical, radiological, and laboratory findings especially seropositivity for NMO-IgG were compatible with NMO. Accurate diagnosis is critical to facilitate initiation of immunosuppressive therapy for attack prevention. This case illustrates that NMO may be associated with SLE.